The Use of the Wakamono Kotoba Egui on “Snow man”'s YouTube Channel - Shabella Widyastuti; Herniwati Herniwati (Universitas Negeri Semarang, 2023)
The purpose of this research is to explain the meaning of the word egui, describe the situations or circumstances in which it is used, and categorize it into meanings and functional types while explaining the contexts of its usage. The research method employed is a qualitative descriptive research technique involving recording and note-taking, with the data source being audio-visual media in the form of 65 videos from the Snow Man YouTube channel. Data analysis involves collecting instances of the word egui from the data source, then analyzing the meaning of egui based on situations or contexts, its usage, meaning categories, and functional types.The results of the research reveal that the word egui has a genuine negative meaning and an expanded positive meaning within the context of wakamono kotoba. The most commonly found positive meanings include praise, such as amazing, great, or extraordinary; the condition such as significant, great, or influential; an expression of admiration, such as cool or wonderful; and a sense of joy. On the other hand, negative meanings are also present, such as when facing difficulties, being troublesome, experiencing hardship, or being in a chaotic situation; or when feeling threatened, in danger, worried, or in a difficult situation. Additionally, there are instances of egui where the meaning can be seen from both positive and negative perspectives, which can be translated into Indonesian as terkejut, kaget, or terperanjat (surprised); as an adjective modifier; or as an honorific term.